DNA damage induction of ribonucleotide reductase. - Elledge, S J (1989)
RNR2 encodes the small subunit of ribonucleotide reductase, the enzyme that catalyzes the first step in the pathway for the production of deoxyribonucleotides needed for DNA synthesis. RNR2 is a member of a group of genes whose activities are cell cycle regulated and that are transcriptionally induced in response to the stress of DNA damage. An RNR2-lacZ fusion was used to further characterize the regulation of RNR2 and the pathway responsible for its response to DNA damage. beta-Galactosidase activity in yeast strains containing the RNR2-lacZ fusion was inducible in response to DNA-damaging agents (UV light, 4-nitroquinoline-1-oxide [4-NQO], and methyl methanesulfonate [MMS]) and agents that block DNA replication (hydroxyurea [HU] and methotrexate) but not heat shock. When MATa cells were arrested in G1 by alpha-factor, RNR2 mRNA was still inducible by DNA damage, indicating that the observed induction can occur outside of S phase. In addition, RNR2 induction was not blocked by the presence of cycloheximide and is therefore likely to be independent of protein synthesis. A mutation, rnr2-314, was found to confer hypersensitivity to HU and increased sensitivity to MMS. In rnr2-314 mutant strains, the DNA damage stress response was found to be partially constitutive as well as hypersensitive to induction by HU but not MMS. The induction properties of RNR2 were examined in a rad4-2 mutant background; in this genetic background, RNR2 was hypersensitive to induction by 4-NQO but not MMS. Induction of the RNR2-lacZ fusion in a RAD(+) strain in response to 4-NQO was not enhanced by the presence of an equal number of rad4-2 cells that lacked the fusion, implying that the DNA damage stress response in cell autonomous.